PENGARUH PROFITABILITAS, SOLVABILITAS, LEVERAGE DAN OPINI AUDITOR TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Stefanus, Stefanus; Wijaya, I Nyoman Agus (LPPM STIE Muhammadiah Bandung, 2025)
This study examines how factors such as profitability, solvency, leverage, and auditor opinion affect audit delay, with firm size considered as a moderating variable. A quantitative research method was employed, focusing on entities listed in the IDX 80 index on the Indonesian stock exchange during the 2021–2023 period. For statistical analysis, moderated regression analysis was conducted using IBM SPSS Statistics version 26. The study's findings reveal that: (1) Profitability and leverage have a significant negative effect on audit delay; (2) Solvency has a significant positive effect on audit delay; (3) Auditor opinion has no significant effect on audit delay; (4) Firm size significantly moderates the effect of profitability and leverage on audit delay; (5) Firm size weakens the influence of solvency and auditor opinion on audit delay; (6) Firm size does not moderate the effect of auditor opinion on audit delay.